The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.molcatb.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic mechanism of human glyoxalase I studied by quantum-mechanical cluster calculations

Abstract: Density functional theory has been used to study the mechanism and stereospeci7icity of the catalytic reaction of human glyoxalase I. We used the quantum mechanical cluster method to model the enzyme active site. Glyoxalase I accepts both enantiomers of the hemithioacetal between methylglyoxal and glutathione and converts them to the S-D enantiomer of lactoylglutathione. We have compared several previously suggested or alternative reaction mechanisms for both substrates on an equal footing. The results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…This confirms the higher basicity of Glu-172 compared to Glu-99, as was previously proposed. [23][24][25][26] The big-QM energies of the four states are compared in Table 1, showing that the S1, S2 and R2 states are almost degenerate, whereas the R1 state is ~4 kcal/mol less stable than the others. In the latter, both protons (H1 and H2) point toward Glu-99, which may destabilize it by steric effects.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This confirms the higher basicity of Glu-172 compared to Glu-99, as was previously proposed. [23][24][25][26] The big-QM energies of the four states are compared in Table 1, showing that the S1, S2 and R2 states are almost degenerate, whereas the R1 state is ~4 kcal/mol less stable than the others. In the latter, both protons (H1 and H2) point toward Glu-99, which may destabilize it by steric effects.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the three studies indicated that the higher basicity and flexibility of Glu-172 may explain the special stereospecificity of GlxI. Despite all previous studies, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] there is not any computationally or experimentally confirmed mechanism for the reaction of the R enantiomer of the normal substrate of GlxI. Moreover, there are two opposing mechanisms for the S substrate and they are based on either a rather primitive ab initio method (HF/4-31G) or a small model of the active site with no constraints on the residues during optimization processes.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations